Theatre Reviews - Heijes, Coen; Georgopoulou, Xenia; Konstantinidis, Nektarios-Georgios (Multicultural Shakespeare: Translation, Appropriation and Performance, 2011)
The Tempest. Dir. Janice Honeyman. The Baxter Theatre Centre (Cape Town, South Africa) and the Royal Shakespeare Company (Stratford-upon- Avon, United Kingdom). As You Like It. Dir. Damianos Constantinidis. “Angelus Novus” Theatre Group, “Vafeio” Theatre. Queen Lear. Dir. Kostis Kapelonis. “Delos G8” Theatre Group, “Delos” Theatre. Hamlet Committed Suicide. Dir. Stella Mari. Street theatre, “Minus [two]” Theatre Group, Thission pedestrian zone (Apostolou Pavlou & Heracleidon). The Documentary. Dir. Sergios Gakas. “Ex Animo” Theatre Group, “Altera Pars” Theatre. Othello. Dir. Yorgos Kimoulis and Konstantinos Markoulakis. Badminton Theatre, Athens, Greece.